Root traits of grasslands rapidly respond to climate change, while community biomass mainly depends on functional composition - Rojas‐Botero, Sandra; Teixeira, Leonardo H.; Prucker, Paula; Kloska, Veronika; Kollmann, Johannes; Le Stradic, Soizig (Functional ecology, 2023)
Current challenges of functional responses in plant communities to climate change call for multi‐factorial experiments. Moreover, studies on climate change should focus on below‐ground responses since absorptive roots largely control soil C allocation and resource acquisition. Thus, we aimed to understand biomass allocation and traits of absorptive roots in young mesocosm grasslands subjected to simultaneous manipulation of three components of climate change. We tested grassland biomass and root traits under climate change while manipulating functional composition. Using 64 mesocosms with designed grasslands within four chambers of a controlled‐environment facility (‘ecotron’), we simulated two contrasting IPCC climate change scenarios for elevated [CO2] and temperature (‘eCO2’ and ‘eT’). We applied normal vs. reduced precipitation of early summer in Central Europe. We also tested the effect of functional composition by varying the proportion of grasses and forbs in the communities. Specifically, we quantified above‐ and below‐ground biomass, root diameter (RD), root tissue density (RTD), specific root length (SRL), and root length density (RLD). Functional composition played a significant role in biomass allocation of the grasslands, with grass‐dominated communities producing more below‐ground biomass than forb‐dominated ones, and the opposite pattern registered above‐ground. Below‐ground biomass did not respond to climate change factors, whereas root trait values responded significantly during early establishment of the grasslands. A higher RD indicated a more conservative strategy under reduced precipitation, while eT and eCO2 led to higher RTD. We detected interactive effects between climate change and functional composition on root traits. Moreover, root biomass primarily occupied the upper soil layer, while a warm and CO2‐rich environment promoted root allocation to the lower soil layer. Grass‐dominated communities quickly colonized all available soil volume, while forb‐dominated ones accumulated more root biomass in the upper soil layer. In the mesocosm grasslands, root trait variation rather than root biomass reflected below‐ground adjustments to climate change. Furthermore, functional composition and the associated trait diversity modulated biomass allocation. Thus, establishing plant communities that are more resilient to climate change must consider the functional and taxonomic composition of the seed mixtures designed to restore urban grasslands. Read the free Plain Language Summary for this article on the Journal blog. Read the free Plain Language Summary for this article on the Journal blog.